2015
DOI: 10.1073/pnas.1514076113
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of HIV-1 protease modulates constitutive eIF2α dephosphorylation to trigger a specific integrated stress response

Abstract: Inhibitors of the HIV aspartyl protease [HIV protease inhibitors (HIV-PIs)] are the cornerstone of treatment for HIV. Beyond their well-defined antiretroviral activity, these drugs have additional effects that modulate cell viability and homeostasis. However, little is known about the virus-independent pathways engaged by these molecules. Here we show that the HIV-PI Nelfinavir decreases translation rates and promotes a transcriptional program characteristic of the integrated stress response (ISR). Mice treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 82 publications
(79 reference statements)
3
66
1
Order By: Relevance
“…To get insight into the mechanisms involved, we treated HeLa cells with 10 lM of NFR and selected and characterized clones that survived and proliferated in the presence of the drug (Fig 1A). NFR concentration can reach up to 17 lM in the plasma of treated patients [25,26] and around 10 lM in liver tissues of mice that receive a dose of NFR reproducing the plasma concentration measured in patients [17]. Up to these concentrations of NFR, we can observe a significant increased viability in the resistant clones compared to the parental population ( Fig 1B).…”
Section: Nelfinavir Resistance Correlates With Decreased Eef2k Expresmentioning
confidence: 54%
“…To get insight into the mechanisms involved, we treated HeLa cells with 10 lM of NFR and selected and characterized clones that survived and proliferated in the presence of the drug (Fig 1A). NFR concentration can reach up to 17 lM in the plasma of treated patients [25,26] and around 10 lM in liver tissues of mice that receive a dose of NFR reproducing the plasma concentration measured in patients [17]. Up to these concentrations of NFR, we can observe a significant increased viability in the resistant clones compared to the parental population ( Fig 1B).…”
Section: Nelfinavir Resistance Correlates With Decreased Eef2k Expresmentioning
confidence: 54%
“…We recently showed that concentrations can reach 10 μM in liver tissues of mice treated with an i.p. dose of NFR reproducing the plasma concentration measured in patients (19). We used the same protocol to interrogate NFRmediated inflammation in mice.…”
Section: Significancementioning
confidence: 99%
“…The HIV-protease inhibitors (HIV-PIs), in particular Nelfinavir (NFR), have been proposed to induce cellular stress both in vivo and in vitro (19,20). Beyond their broad use as anti-HIV drugs, these molecules display beneficial HIV-unrelated functions, antimalaria, antituberculosis, and antitumor properties (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a previous study we showed that NFR targets translation program by inducing the integrated stress response (ISR). 4 This response is driven by the phosphorylation of the translation initiation factor eIF2a to decrease overall translation initiation and increase production of stress factors including the transcription factor ATF4. While the ISR is a key response that modulates cellular homeostasis, this pathway did not affect cellular viability in presence of the HIV-PIs.…”
mentioning
confidence: 99%